2011
DOI: 10.31018/jans.v3i2.210
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic induced genotoxic and histopathological changes in male Swiss albino mice, Mus musculus

Abstract: The present study was carried out to investigate the effect of arsenic trioxide on the DNA and histomorphology of testis, liver and kidney of Swiss albino mice, Mus musculus. Oral administration of arsenic trioxide induced DNA damage in the testis, liver and kidney marked by light pink staining of nuclei after Feulgen's reaction with reduced fine chromatin. Simultaneously severe histological changes were noted like distortion of seminiferous tubules, disorganization of spermatogonia, spermatocytes and spermati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Tartrazine can affect the blood cell formation and may cause the abnormal sized erythrocytes. Studies in swiss albino mice reported similar changes in MCH treated with tartrazine [27]. In chronic experiments, MCH was decreased in test fishes in accordance with the increasing concentration of exposed tartrazine.…”
Section: Haematological Changes In Fishesmentioning
confidence: 52%
“…Tartrazine can affect the blood cell formation and may cause the abnormal sized erythrocytes. Studies in swiss albino mice reported similar changes in MCH treated with tartrazine [27]. In chronic experiments, MCH was decreased in test fishes in accordance with the increasing concentration of exposed tartrazine.…”
Section: Haematological Changes In Fishesmentioning
confidence: 52%
“…Disruption of hepatocytic plates, the breakdown of hepatocytes evidenced by cell membrane rupture, cytoplasmic vacuolization, and nuclear pycnosis were all signs of histological changes in the liver tissue of Cd-treated rats. (Mohapatra et al, 2013). and ElRefaiy (2020) who observed severe hepatic The histological alterations seen in livers treated with Cd may be explained by the production of extremely reactive radicals and subsequent lipid peroxidation.…”
Section: Discussionmentioning
confidence: 96%